Needle revision outcomes after glaucoma filtering surgery: survival analysis and predictive factors. Issue 2 (March 2020) - Rabiolo, Alessandro; Marchese, Alessandro; Bettin, Paolo; Monteduro, Davide; Galasso, Mario; Dolci, Maria Paola; Di Matteo, Federico; Fiori, Marina; Ciampi, Carlo; Bandello, Francesco
Purpose: To evaluate the efficacy and safety of needle revision and examine factors predictive of failure. Methods: In total, 157 eyes of 131 patients that underwent needle revision augmented with either 5-fluorouracil or betamethasone for trabeculectomy failure were included in this retrospective study. Complete failure was defined as additional glaucoma surgery, ciliodestructive procedures, loss of light perception, sight-threatening complications, hypotony maculopathy, and surgical bleb revision. Success was defined as intraocular pressure ⩽ 18 (criterion A), ⩽15 (criterion B), and ⩽12 mmHg (criterion C) reached with (qualified) or without (complete) medications, and absence of any criteria of complete failure. Results: The median (interquartile range) follow-up was 25.0 (41.0) months. Complete failure rates were 19%, 26%, and 31% at 1, 2, and 3 years, respectively. For criterion A, qualified and complete success rates were, respectively, 77% and 69% at 1 year, 66% and 51% at 2 years, and 60% and 47% at 3 years. For criterion B, qualified and complete success rates were, respectively, 67% and 61% at 1 year, 48% and 42% at 2 years, and 44% and 39% at 3 years. For criterion C, qualified and complete success rates were, respectively, 43% and 41% at 1 year, 27% and 25% at 2 years, and 24% and 23% at 3 years. High baseline intraocular pressure and primary surgery were associated with higher and lower risks of complete failure, respectively. Conclusion: Needle revision is an effective and safe procedure to rescue failing trabeculectomy postponing or avoiding further glaucoma surgery. Eyes with low target intraocular pressure may have poor long-term outcomes.